Older Adults’ Life Satisfaction: The Roles of Seeking Financial Advice and Personality Traits - Swarn Chatterjee; Lu Fan (Journal of Financial Therapy, 2021)
This paper uses 1,237 respondents from the Health and Retirement Study dataset to examine the relationships among personality, financial advice-seeking, and life satisfaction of U.S. older adults. The results indicate that extraversion is negatively associated with seeking professional financial advice, while conscientiousness and openness were associated positively with seeking professional financial advice. Individuals with a neurotic personality trait were positively associated with seeking financial advice from families and friends. Additionally, seeking professional financial advice, and being extraverted and conscientious, were positively associated with life satisfaction among older adults. The implications for financial therapists and counselors include suggestions for implementation of cross-functional collaborative counseling strategies when working with older clients who may be experiencing physical and mental health-related problems. Implications of the findings for policymakers are also discussed.
Keywords: Financial help seeking; financial therapy; life satisfaction; personality; cognitive ability; health status; elderly